Águas do semiárido: mulheres rurais e o acesso a cisterna para consumo humano no município de Serrinha-Bahia - Jesus, Selma Glória de (2020)
The subordinate conditions historically experienced by women in Brazilian semiarid are due to gender inequalities, linking them to the spaces in the private sphere, and so charged with responsibility for water supply and care for domestic needs and non-participation in decision-making. Social technologies implemented (in rural communities) in the city of Serrinha has incorporated in the gender’s perspective and mobilized actions that interfere in the socio-political, economic and cultural questions. In this context, the objective of this study is to analyze the access of rural women to the policy of water cisterns for human consumption and to know to what extent this access has contributed to their economic autonomy and socio-political participation. This is a qualitative research based on semi-structured interview, and thematic workshops, with the use of graphic systematization accomplished by women and the leaders of social organizations that integrated the Municipal Water Commission. The results of this study point out the great challenges to live in areas with long periods of drought, parallel to little access to water, which promotes many difficulties for women, besides to increase the sexual division of domestic work. The few opportunities offered to them, in view of the gender and race inequalities present and insufficient participation in decision-making related to water policy. On the other hand, we identity the women’s performance in several organizations that articulate around policies of coexistence with the semiarid region, both in community and municipal and regional actions that reveals a process of becoming aware about their rights and the oppressions lived, in order to lead fights and conquests. We highlight, the need to policy makers to incorporate gender equity at all levels of their elaboration and implementation, as well as civil society organizations to establish synergy with the women's agenda and recognize them like autonomous political people. Like this, it is necessary to feed on by learning, experience and knowledge from the rural women who search in a resistant and resilient way build alternatives for good living in the semiarid.